Analisis Makna Tabarruj dalam Al-Qur’an Surah Al-Ahzab Ayat 33 - Widia Astika; Khairunnisa Syamsu; Muhammad Rezky; Danial; Hasan Basri (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to examine tabarruj in Q.S al-Ahzab verse 33. And how to understand the meaning of tabarruj in the Qur'an. This research uses library research method. The primary sources in writing this article include references that discuss implicitly or explicitly about tabarruj in the Qur'an. The obtained references are then edited, reduced, verified and analyzed, to be further studied further in order to find the right understanding related to tabarruj. The results of this research and discussion show that tabarruj behavior from the jahiliyah period to the present is still being carried out. This study concludes that the tabarruj interpreted in the Qur'an and the tabarruj that occur today are still very contradictory. This study also recommends that tabarruj behavior is contrary to the instructions of the Qur'an so that it must be understood with the right understanding.